Appraisal biases about strangers in posttraumatic stress disorder - Sachschal, J; Woodward, E; Ehlers, A (Springer, 2018)
Cognitive theories of posttraumatic stress disorder (PTSD) suggest that negative appraisals play an important role in the development and maintenance of PTSD. It has not yet been examined experimentally how people with PTSD appraise strangers. Twenty-two trauma survivors with PTSD and 26 non-traumatised controls completed a person impression updating task. There was no group difference in initial kindness ratings of people shown in the photos. The PTSD group changed their ratings more when receiving negative compared to positive information about the person, relative to controls. When incongruent information was subsequently presented, the PTSD group tended to be more influenced by negative information than positive information, relative to congruent information, than controls. The findings suggest selective attention to negative information about others in PTSD.